ФАРҒОНА БОТИҒИНИНГ ГЕОМОРФОЛОГИК ТУЗИЛИШИНИ ЎРГАНИШ - Қўзибоева, О.; Расулов, Э. (SCIENCE and SOCIETY, 2021)
The geomorphological,geoglogic and tectonic structure of the landscapes of the Fergana wreck at different periods is illuminated. In-depth analysis of the geomorphological structure and relief-forming factors of the Fergana wreck, the publication of the results and their improvement in certain stages has been studied.